German sports clubs' recruitment of executive board members - Eike Emrich; Monika Frenger; Freya Gassmann; Martin Hämmerle; Christian Pierdzioch (Europäisches Institut für Sozioökonomie e. V., 2019)
This paper analyzes the recruitment of executive board members for German sports clubs, an issue of key interest given that volunteers play a dominant role in these sports clubs. Based on a new, micro-level data set, we examine how members of a sports club advance to become executive board members and how board members differ from ordinary members. Based on the results of our study, we examine whether Michels' "iron law of oligarchy" applies and whether democratic procedures for elections in sports clubs are replaced, even in part, by trust-based oligarchic structures.
urn:nbn:de:bsz:291–ds-322864; hdl:20.500.11880/29747
Keywords: 300; Sports; volunteering; oligarchy; sports clubs; executive boards; Ehrenamt; Oligarchie; Sportverein; Vorstand